Analysis of exosome-derived microRNAs reveals insights of intercellular communication during invasion of breast, prostate and glioblastoma cancer cells. Issue 1 (1st January 2021) - Lessi, Francesca; Aretini, Paolo; Rizzo, Milena; Morelli, Mariangela; Menicagli, Michele; Franceschi, Sara; Mazzanti, Chiara Maria
ABSTRACT: MiRNAs represent a mechanism that regulates gene expression in many pathological conditions. Exosomes are known to be secreted from all types of cells, and the exosomes-released molecules are crucial messengers that can regulate cellular processes. We investigated the miRNAs content of exosomes released by cancer cells during the invasion . An invasion stimulus has been generated through scratches created on the confluent cells of cancer cell lines: glioblastoma, breast and prostate cancers. Several miRNAs were found to be significantly differentially abundant during the cell invasion, both in common among different cell lines and exclusive. Understanding the language codes among cells involved in invasion can lead to the development of therapies that can inhibit cellular communication, slowing or eventually stopping their activity.